Interventions to Reduce Racial and Ethnic Disparities in Health Care - Chin, Marshall H. (2007)
In 2005, the Robert Wood Johnson Foundation created Finding Answers: Disparities Research for Change, a program to identify, evaluate, and disseminate interventions to reduce racial and ethnic disparities in the care and outcomes of patients with cardiovascular disease, depression, and diabetes. In this introductory paper, we present a conceptual model for interventions that aim to reduce disparities. With this model as a framework, we summarize the key findings from the six other papers in this supplement on cardiovascular disease, diabetes, depression, breast cancer, interventions using cultural leverage, and pay-for-performance and public reporting of performance measures. Based on these findings, we present global conclusions regarding the current state of health disparities interventions and make recommendations for future interventions to reduce disparities. Multifactorial, culturally tailored interventions that target different causes of disparities hold the most promise, but much more research is needed to investigate potential solutions and their implementation.